(untitled) (Journal of Pharmaceutical Negative Results, 2022)
This research examined the effect of irradiation on the synthetic properties of the SnO2/n-Si membrane. The prepared membrane was prepared by vacuum fumigation and irradiated with 1.33Mev energy Gama rays, time periods and radiation doses (3h × 14Gy), (24 h × 14 Gy) and (3d × 14Gy).Synthetic properties were studied through XRD screening before and after irradiation. The results of the study showed that exposure of the membrane to Gama rays and through XRD screening for three hours resulted in a decrease in relative intensity at the angle and a severe decrease in relative intensity at the angle. (150) with a slight increase in the intensity value at the angle Ɵ=44.24982 this indicates crystal growth when irradiation increases for a day. When irradiated for three days, the relative intensity at the angle decreased Ɵ=59.18402 indicating crystal defects that reduced the value of crystallization, accompanied by an increase in intensity at the Ɵ=44.24982 and Ɵ=25.87862 angles. Increased irradiation has, by examining XRD, clearly affected the improvement of synthetic properties. The characteristics of the current-voltage were also examined by forward and reverse biases in darkness and reverse only when illuminated by the M1 light current equal to 0.24. From the M4 specimen, there is an increase in the light current. The value of the light current at radiation increased for one day at the same intensity to the 0.31 and this value continued to improve when irradiated for three days, as the value rose to 0.45. (1-2-3) The time of inertia decreased from (2.3) to (1.2) and this time of inertia at irradiation for three days is evidence of many disruptions that have led to an increase in the total value of the detector resistance resulting in an increase in the time of inertia.